LoRa‑based Self‑organized Network Health Monitoring System - SHI Haoning; YANG Kun; SANG Shengbo; YANG Jia; LI Shengjia (Taiyuan Ligong Daxue xuebao)
[Purposes] With the development of low-power wide area networking technology and microsensors, they have been widely used in wearable devices, achieving better transmission of vital sign monitoring data. However, existing techniques such as Bluetooth and Wi-Fi have difficulties in networking in scenarios such as nursing homes and other multi-node network monitoring, and because of sensor volume limitations, blood pressure cannot be effectively monitored. In this article, an ad hoc network human vital sign detection system based on LoRa communication technology is designed and implemented. [Methods] After the system nodes solving the heart rate, blood oxygen, body temperature, and human PPG waveform feature vector through local calculation, a self-organizing network was constructed by using the LoRa RF chip to upload multi-node data to the gateway and then to the server’s network. The server used BP neural network to calculate blood pressure data, and the analysis results were synchronized to the node display through the monitoring network. [Results] The experimental results show that the system can achieve normal communication among 7 node terminals, with a communication distance of up to 1.55 km, and physiological parameter errors within 5%. The blood pressure monitoring effect meets the blood pressure measurement standard of the American Association for the Advancement of Medical Instrumentation (AAMI). [Conclusions] The prosoed system has broad application prospects in nursing, elderly care monitoring, and other scenarios.